PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS TERPADU DI SMP NEGERI 1GUNUNG SITOLI UTARA - Ahmadsyukur Baene; Arianto Lahagu (Jurnal Tunas Pendidikan, 2023)
The aim of this study; (1) To find out the application of the Problem Solving learning model to the Integrated IPS subject; (2) To find out student learning outcomes through applying the Problem Solving Learning Model in Integrated IPS subjects; (3) knowing the increase in student learning outcomes through the Application of the Problem Solving Model. in class VIIIUPTD SMP Negeri 1 Gunungsitoli Utara for the Academic Year 2022/2023. This research is Classroom Action Research (CAR). The research instrument was in the form of teacher and student observation sheets, learning achievement tests and documentation. This research was conducted in class VIII even semester UPTD SMP Negeri 1 Gunungsitoli Utara for the 2022/2023 academic year. The number of students is 26 people with 12 boys and 14 girls. Based on the results of this study it is known that; (1) Observations for teachers in the first cycle reached an average of 62.49% while in the second cycle the teacher's ability to implement the learning process increased to 87.49%. Observations of student activity in the first cycle reached an average of 60.46%. and in cycle II it reached an average of 85.04%; (2) in the first cycle the average student learning outcomes is 68.87 while in the second cycle the average student learning outcomes is 83.90; (3) The percentage of completeness achieved in cycle I was 61.53% while the percentage of completeness in cycle II was 84.61%. The results of the study showed that there was an increase in student learning outcomes in the Integrated Social Studies subject through the application of the Problem Solving learning model in class VIII-UPTD SMP Negeri 1 Gunungsitoli Utara for the 2022/2023 academic year.